Evaluasi Pengaruh Parameter TIM Berdasarkan Multirate Terhadap Konsumsi Energi Jaringan IEEE 802.11ah - Daifi Afrila Riefi; Teuku Yuliar Arif; Syahrial (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
WLAN IEEE 802.11ah is wireless standard technology which potentially used for IoT networking to provide longer range transmission than WPAN and LPWAN. MAC layer IEEE 802.11ah introduces TIM segmentation scheme that provides effective management toward STA in large amount to make the energy consumption efficiently. STA is organized in hierarchical structure that allows TIM segmentation to reduce the length of frame beacon contains TIM. In case there’s no segmentation in a network with many STA, the TIM would be longer and requires all STA to wake-up receiving beacon TIM including STA without downlink data. This research intends to evaluate and analyze the TIM optimal parameters. Those are Page Period, Page Slice Length and Page Slice Count toward IEEE 802.11ah energy efficiency based on multirate using simulator NS-3 implemented on IEEE 802.11ah. As the result of STA experiment shows that Non-TIM is only optimal on sleep duration while TIM is optimal on energy consumption and delay packet. In the experiment of impact of STA/Slot amount based on Page Slice Length shows that sleep duration and energy consumption is optimal depends on the amount of the STA/Slot and data rate used while the optimal packet delay varies for each Page Slice Length.